2002
DOI: 10.1007/s00213-002-1243-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of benzodiazepines on structural and conceptual/lexical priming

Abstract: Equivalent priming for identical and complementary pictures in the three groups suggests that benzodiazepines do not affect the activation of the geon structural description. The lack of priming for same-name pictures suggests that benzodiazepines affect access, retrieval or selection of conceptual/lexical information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
(46 reference statements)
0
7
1
Order By: Relevance
“…In previous studies using a category generation task, Brown et al11 found conceptual priming to be suppressed with lorazepam, while Bishop and Curran17 reported that conceptual priming is preserved under lorazepam. And results on conceptual priming using a same-name exemplar test reported conceptual/lexical priming to be suppressed in participants administered with a single dose of lorazepam 42. The present experimental study did not find any differential effect of lorazepam compared to diazepam and placebo on conceptual priming at Day 2 of the experiment.…”
Section: Discussioncontrasting
confidence: 55%
“…In previous studies using a category generation task, Brown et al11 found conceptual priming to be suppressed with lorazepam, while Bishop and Curran17 reported that conceptual priming is preserved under lorazepam. And results on conceptual priming using a same-name exemplar test reported conceptual/lexical priming to be suppressed in participants administered with a single dose of lorazepam 42. The present experimental study did not find any differential effect of lorazepam compared to diazepam and placebo on conceptual priming at Day 2 of the experiment.…”
Section: Discussioncontrasting
confidence: 55%
“…More constrained situations could also explain previous effects of lorazepam in tests that involved identification of degraded pictures (e.g. Boucart et al 2002;Sellal et al, 1992;Vidailhet et al, 1994;Wagemans et al, 1998), an effect not observed here in the Gestalt Completion task in which subjects were exposed to all degraded pictures for 2 min and could concentrate on any of them for periods varying in length as they saw fit. Also, this task was found to be difficult even for placebo-treated subjects, so it can say little about the perceptual effects of lorazepam.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, the dose of lorazepam used here was sufficiently high to elicit the classic BZ episodic memory effects, and has also been shown to atypically impair performance in perceptual implicit memory measures such as stem completion (Blin et al, 2001;Buffett-Jerrott et al, 1998;Pompéia et al, 2000Pompéia et al, , 2003aStewart et al, 1996;Thiel et al, 2001) and identification of degraded pictures (e.g. Boucart et al 2002;Sellal et al, 1992;Vidailhet et al, 1994;Wagemans et al, 1998). Whether the underlying mechanisms responsible for results in the Identical Pictures are related to the atypical visual perceptual effects of lorazepam (e.g.…”
Section: Discussionmentioning
confidence: 87%
“…GABA A PAMs may reduce familiarity by attenuating semantic or implicit memory processes that are thought to support feelings of familiarity (Yonelinas, 2002; also see Wang et al, 2014; Davies et al, 2004). Although GABA A PAMs do not always affect implicit or semantic memory (for review, see Curran, 1999), there are some cases in which they can (e.g., Hirshman, Passannante, & Henzler, 1999; Stewart et al, 1996; Boucart et al, 2002).…”
Section: Discussionmentioning
confidence: 99%